Patients with cancer experience high impact of emotional consequences of reduced ability to eat: A cross sectional survey study. (27th April 2022) - Lize, Nora; Raijmakers, Natasja; van den Berg, Manon; Emmaneel, Leontien; Kok, Annemieke; Lagendijk, Marlies; van Leeuwen‐Bouwhuis, Kim; van Lieshout, Rianne; Nagel, Zola; Beijer, Sandra
Abstract: Objective: Patients with cancer can experience emotional consequences of reduced ability to eat, their impact is unknown. This study assesses the impact of these emotional consequences, and patients' satisfaction with healthcare professionals' (HCPs) support. Methods: A cross‐sectional survey was conducted among patients with head/neck, lung cancer and lymphoma, who experienced reduced ability to eat in the past year. Patients were recruited through patient organisations and hospitals. The questionnaire encompassed the impact of emotional consequences of reduced ability to eat (scale 1–10) and satisfaction with HCPs' support for reduced ability to eat (scale 1–10). The differences in patient characteristics between unsatisfied (Score < 6) and satisfied patients (score ≥6) were tested using independent t ‐tests and the chi‐square or Fishers' exact tests. Results: Overall, 116 patients (48%) responded and 98 were included in the analyses. The most impactful emotional consequences were as follows: disappointment (mean ± SD: 8.31 ± 1.49), grief/sadness (7.90 ± 1.91), and anger (7.87 ± 1.41). Patients were less satisfied when more time had passed since their diagnosis ( p < 0.002) and when they expected no improvements regarding their eating problems ( p < 0.001). Conclusion: The impact of emotional consequences of reduced ability to eat is high. Support for emotional consequences is needed, especially for patients with reduced ability to eat, which persists in recovery and remission.